Do lipid microemboli induce acute kidney injury during cardiopulmonary bypass?. (September 2017) - Issitt, Richard; James, Tim; Walsh, Bronagh; Voegeli, David
Background: Acute kidney injury (AKI) following cardiopulmonary bypass affects 5% of patients, representing significant postoperative morbidity and mortality. Animal models have shown an increased uptake of lipid microemboli (LME) into the renal vasculature, potentially indicating ischaemic causation. This study tested a new lipid filtration system (RemoweLL) against a conventional system with no lipid-depleting capacity to determine the efficacy of the filtration system and its effects on renal function. Methods: Thirty consecutive patients underwent coronary artery bypass graft surgery using either the RemoweLL filtration system (15 patients) or a conventional cardiopulmonary bypass circuit (15 patients). Renal function was assessed using cystatin C concentrations as a surrogate marker of glomerular injury, as well as perioperative glomerular filtration rate (GFR) and serum creatinine concentrations. Patients were defined as having acute renal injury if there was an increase in absolute serum creatinine ⩾3 mg/dL (26.4 µmol/L) or 1.5-fold increase from baseline as categorised using the AKIN criteria. Results: Postoperative differences in LME count between the two groups were highly significant [p<0.001]. Analysis of peak cystatin C concentrations showed significantly lower levels in the LME filtration group on the 2 nd postoperative morning [p=0.04]. Two-factor ANOVA revealed a trend towards interaction, but this failed to reach significance [p=0.06]. There were no differences throughout the study period in serum creatinine or GFR [p>0.05]. There were no differences in any of the serum or urinary electrolytes. Conclusions: This study has shown a trend towards improved cystatin C removal with LME filtration; with significantly lower peak concentrations, although no further evidence of renoprotection could be demonstrated. Further research is warranted to establish possible renal benefits of LME filtration in patients undergoing cardiac surgery.